Chercheurs en interaction avec le terrain corse - Catherine Herrgott (In Situ)
The ethnomusicological collections and analyses carried out in Corsica since Félix Quilici's first collecting campaign in 1948, by Wolfgang Laade and by Markus Römer, are pioneering and essential fieldwork. In the 1970s, the emphasis was placed on the phenomenon of identity and the process of identity, orality and then creation in the 1980s and 1990s. This second phase of collecting, to which I associate the studies on Franciscan sacred polyphony compiled by Marcel Pérès (1996) and the work of the Italian ethnomusicologist Ignazio Macchiarella on falsobordone (1995), lasted some thirty years until the early 2000s and was marked by a strong male pregnancy among both researchers and practitioners/collectors. From the 2000s to the present day, interest has focused more particularly on the phenomenon of invention (or reinvention), on the processes of making traditional music part of our heritage and on the spectacularisation of music in the oral tradition. Young researchers are currently carrying out acoustic and articulatory analyses based on polyphonic vocal material collected in 2014. While the question of the relationship between allochthonous and autochthonous researchers and the field runs through the three phases of the period under consideration, the last phase raises the issue of the rather unprecedented relationship between non-insular researchers and the Corsican field.